Becoming yellow : a short history of racial thinking - Keevak, Michael, 1962- (Princeton University Press, 2011)
In their earliest encounters with Asia, Europeans almost uniformly characterized the people of China and Japan as white. This was a means of describing their wealth and sophistication, their willingness to trade with the West, and their presumed capacity to become Christianized. But by the end of the seventeenth century the category of whiteness was reserved for Europeans only. When and how did Asians become "yellow" in the Western imagination? Looking at the history of racial thinking, Becoming Yellow explores the notion of yellowness and shows that this label originated in the eighteenth- and nineteenth-century scientific discourses on race